A comparative study on outcome of endonasal dacryocystorhinostomy with and without silicone intubation-otorhinolaryngology - Karkare, Ajay; Singh, Arvind (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Epiphora or “tearing eye” is a functionally and socially, bothersome symptom. Dacryocystitis is an inflammatory condition of the nasolacrimal sac caused due to an obstruction within the nasolacrimal duct (NLD). Dacryocystitis can be classified as acute and chronic or acquired and congenital. Chronic dacryocystitis is almost always managed surgically. The present study was undertaken for comparative study of outcomes of endonasal Dacryocystorhinostomy (DCR) done with and without silicone intubation. Methods: The 50 cases dacryocystitis were selected. The patients were divided in group A cases (with intubation) and group B controls (without intubation) randomly. A detailed history was taken followed by general physical and clinical otorhinolaryngological examination. Patients were evaluated with nasal endoscopy, DCG (Dacrocystogram), through which site of obstruction was located. Results: In our study, Among the cases 18 subject presented with right dacryocystitis and 7 with left dacryocystitis. Similarly, among the controls, 20 subjects presented with right dacryocystitis and 5 presented with left dacryocystitis. According to modified Likert’s score, at the end of 6 months when a nasal endoscopy was done along with syringing 96% of the cases had patent rhinostomy while only 80% of the controls showed patency. Post operative epistaxis was evident in 6 cases and 4 controls. Conclusions: Endonasal DCR with and without stenting, had more or less similar results, with equal post op complications. Though, with stenting, success rates were high as shown in our study.